Kultura jako czasownik Sondowanie nowej humanistyki - Nycz, Ryszard (Nowa Humanistyka, 2017)
Culture as a Verb is a book on what I call new humanities of a wide and vastly varied orientation, direction, turns, and simply interests, interconnecting in opposition to the principles of contemporary theory of humanistic cognition. For, if contemporary knowledge is presented as bodiless, impersonal, static, external and neutral (unengaged), then the new humanities inquiries are led on the basis of different principles: embodied knowledge, personalised (participating), actively-acting (intervening cognitively), penetrating the research field and situated (engaged). This is a very significant change . . . With it, we go from a culture of disinterested observation, founded on the myth of the contemplative view of the whole external world, to a real culture of participative action, reconciled with perspectivity and the fragmentary nature of cognitive actions of a subject, who forges a path to reality, from within and by their own actions.